PENGARUH PENGUMUMAN LIKUIDASI BANK TERHADAP MINAT MENARIK UANG DARI BANK - Haribowo, Ignatius Novianto (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2017)
AbstractThis study aims to examine the factors that influence a person to withdraw all or part of the money from the bank in liquidation of large banks case in Indonesia. This study uses the theory of Lewin to uncover factors that may influence a person to withdraw part or all of the money from the bank if there is a big bank liquidation. Based on Lewin's theory, there are two factors that can influence a person's decision, namely internal factors and external factors. Internal factors in this study are trust and cognitive absorption, while external factors in this study are the social norm, interference of others, government supervision. This study use questionnaire to examine the factors from respondents. Processing data results using Partial Least Square (PLS) indicates that external factors influence someone's decision to keep the money in the bank if there is big bank liquidation more than internal factor. These indicates that the condition of society is easy to change depend on the external situation. The results also indicate a lack of trust to the bank institutions.Key words: Lewin Theory, Internal Factor, External Factor, Partial Least Square (PLS).